DIGITAL MEDIA AND EMPLOYEE INTEGRITY IN REJECTING GRATIFICATION: A CASE STUDY OF ORGANIZATIONAL COMMUNICATION AT USU HOSPITAL - Thoriq Mursyidan; Mutiara Desiana; Achmad Darmawan; Abdullah Alfath (OPINI: Journal of Communication and Social Science, 2026)
This study examines the role of digital media in organizational communication in strengthening employee integrity, particularly in rejecting gratification practices within healthcare institutions. Using a qualitative case study approach at the University of North Sumatra Hospital, data were collected through in-depth interviews, participatory observation, and document analysis involving 15 informants selected purposively. The findings reveal that digital media function not only as communication tools but also as a cultural infrastructure that reinforces integrity values through continuous exposure, transparency, and interactive systems. Digital platforms such as intranet systems, integrity dashboards, and online reporting mechanisms enhance information accessibility and foster employees’ confidence in rejecting and reporting gratification. Furthermore, digital communication contributes to ethical behavior formation through cognitive recall, norm internalization, and social learning processes. This study proposes the Digital Integrity Communication Model (DICM) as a theoretical contribution, emphasizing the integration of technology, organizational values, and behavior in shaping organizational image and trust.